Experimental study of the effects of graphene oxide on microstructure and properties of cement paste composite. (November 2017) - Yang, Haibin; Monasterio, Manuel; Cui, Hongzhi; Han, Ningxu
Abstract: Graphene oxide (GO) has been utilized to strengthen composite materials. In this study, the effects of GO on hydration degrees, macro-mechanical strength and calcium-silicate-hydrate (C-S-H) structure of cement based composites were investigated through comprehensive experimental tests. In addition, the aggregation mechanism of GO was verified by alkaline solution simulations, using Ca(OH)2 and NH3 ·H2 O. Based on the experimental results, it was found that the 3-day and 7-day compressive strengths of cement based composites with 0.2 wt% of GO were increased by 35.7% and 42.3%, respectively as compared to the control. Moreover, the C-S-H structure of cement paste with GO was not observed to have undergone any change via qualitative and quantitative analyses combined with FT-IR, XRD and 29 Si-NMR. Besides, the test results of TGA, DTG and 29 Si-NMR showed that the hydrated degree of cement paste increased to 10.4% at 28 days when incorporating with 0.1% of GO.